2018
DOI: 10.3389/fimmu.2018.01746
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Schistosoma mansoni Cleave the Host Immune and Hemostatic Signaling Molecule Sphingosine-1-Phosphate via Tegumental Alkaline Phosphatase

Abstract: Schistosomes are parasitic flatworms that infect the vasculature of >200 million people around the world. These long-lived parasites do not appear to provoke blood clot formation or obvious inflammation around them in vivo. Proteins expressed at the host–parasite interface (such as Schistosoma mansoni alkaline phosphatase, SmAP) are likely key to these abilities. SmAP is a glycoprotein that hydrolyses the artificial substrate p-nitrophenyl phosphate in a reaction that requires Mg2+ and at an optimal pH of 9. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 66 publications
(97 reference statements)
0
39
0
Order By: Relevance
“…Mechanistically, there is strong evidence indicating that that schistosomes directly modulate the host haemostatic system via a variety of bioactive secretory products and molecules on the schistosome's outer-surface (tegument) (9). For instance, schistosomes inhibit blood clot formation and/or promote blood clot lysis through the activities of several tegumental enzymes, including enolase, SmSP2, SmAP and SmCalp1&2, and vascular tone is modified through the activities of SmSP2 and SmPOP (3236). Altogether, such processes can be viewed as a schistosome survival mechanism in the blood stream, likely promoting residence and movement while preventing unwanted vessel occlusion.…”
Section: Endothelial Extravasationmentioning
confidence: 99%
“…Mechanistically, there is strong evidence indicating that that schistosomes directly modulate the host haemostatic system via a variety of bioactive secretory products and molecules on the schistosome's outer-surface (tegument) (9). For instance, schistosomes inhibit blood clot formation and/or promote blood clot lysis through the activities of several tegumental enzymes, including enolase, SmSP2, SmAP and SmCalp1&2, and vascular tone is modified through the activities of SmSP2 and SmPOP (3236). Altogether, such processes can be viewed as a schistosome survival mechanism in the blood stream, likely promoting residence and movement while preventing unwanted vessel occlusion.…”
Section: Endothelial Extravasationmentioning
confidence: 99%
“…In agreement with a previous report (Argiro et al, 2000a), SmGAPDH displays optimal enzyme activity at a pH of ∼9.2, suggesting that, in the relatively neutral pH of the bloodstream, any surface SmGAPDH activity might be tempered. It is noteworthy that several surfaceexpressed schistosome enzymes also display alkaline pH optima (Cesari et al, 1981;Da'dara et al, 2014;Elzoheiry et al, 2018a). SmGAPDH, like GAPDH enzymes from other species, displays no requirement for divalent ions for its catalytic activity (Maurer et al, 2015;Kim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the worms possess a series of ectoenzymes that are thought to impact this process: the surface diphosphohydrolase SmATPDase1 and the surface phosphodiesterase/pyrophosphatase SmNPP5 can both cleave the platelet activator adenosine diphosphate (ADP) (Elzoheiry et al, 2018b), and, as shown for SmNPP5, this can block platelet aggregation in vitro (Elzoheiry et al, 2018b). The surface ectoenzyme alkaline phosphatase SmAP can cleave the procoagulant lipid mediator sphingosine-1-phosphate (Elzoheiry et al, 2018a) as well as the prothrombotic polymer polyphosphate (polyP) (Elzoheiry et al, 2019). In addition, host-interactive tegumental proteases can cleave key components of the coagulation cascade such as fibronectin (Wang et al, 2017) and high-molecular-weight kininogen (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This view was supported by Perez and Terry (1973) where they observed that the surface of the schistosome was turning over more rapidly when schistosomes cultured in monkey antimouse serum were selected from the schistosome mice model. This unique membrane structure allows the schistosome tegument to play a significant role in protecting the schistosome to survive in the host, some of which include; host response modulation that causes host immune response evasion (Elzoheiry et al, 2018). This immune evasion occurs by rendering the infected host's antibody responses ineffective, hence fails to clear the established parasites (Han et al, 2009).…”
Section: Metrifonatementioning
confidence: 99%